Association of an Increased Risk of Pre-eclampsia and Fetal Growth Restriction in Singleton and Twin Pregnancies with Female Fetuses. Issue 1 (9th January 2021) - Bi, Shilei; Zhang, Lizi; Wang, Zhijian; Tang, Jingman; Xie, Sushan; Gong, Jingjin; Lin, Lin; Ren, Luwen; Huang, Lijun; Zeng, Shanshan; Chen, Jingsi; Du, Lili; et al.
Abstract: Objective: To investigate whether the fetal gender affects the incidence of pre-eclampsia (PE) and fetal growth restriction (FGR) in singleton and twin pregnancies. Methods: This was a 10-year single-center, retrospective, cohort study from January 2009 to January 2019. A total of 57, 129 singleton and 3699 twin pregnancies aged between 18–55 years old were recruited at the Third Affiliated Hospital of Guangzhou Medical University, China. We used multivariable logistic regression to analyze the effect of fetal gender on the incidence of PE and FGR. Results: In singleton pregnancies, the incidence rates of PE and FGR with a female fetus were higher than those with a male fetus (6.4% (1713/26, 793) vs . 5.9% (1803/30, 336), P < 0.05 and 3.5% (932/26, 793) vs. 2.4% (745/30, 336), P < 0.05, respectively). A female fetus was an independent risk factor for either PE or FGR (adjusted odds ratio: 1.169 or 1.563; 95% confidence interval: 1.036–1.319 or 1.349–1.810, respectively). In twin pregnancies, the incidence of early-onset PE was greater in pregnancies with two females compared with two males or one male plus one female (4.6% (46/1003) vs. 4.1% (54/1305) vs. 2.4% (33/1391), P < 0.05). Female-female twins was an independent risk factor for PE (adjusted odds ratio: 1.367, 95% confidence interval: 1.011–1.849), especially early-onset PE. Conclusion: The female fetus was associated with PE in both singleton and twin pregnancies and was also a risk factor of FGR in singleton pregnancies.